CIRCULATING OVARIAN STEROID PROFILES IN SURTI BUFFALOES SUPEROVULATED WITH FSH AND DIFFERENT DOSES OF PMSG
Eighteen Surti buffaloes of 2 to 6 lactations were superovulated during breeding season (August to February) using FSH and 2 doses of PMSG. Animals were divided into three groups. Group I (n=6) and Group II (n=6) donors were superovulated with single Vm dose of 2500 and 3000 IU PMSG, respectively, on day 10 of the estrous cycle, whereas Group Ill (n=6) donors were treated intramuscularly with 400 mg FSH per donor in 8 equal doses 12 hours apart for four days. Jugular samples were collected from all donors at five different stages of MOET, i.e, Day O (Heat), Day 1 O (PMSG treatment), Day 12 (2nd PGF 24 inj. ), Day 14 (Superovulatory estrus) and Day 20 (Flushing